Mapping the Ionosphere Over East Asia Based on Ground‐Based GNSS TEC Data in 2010–2023 - Yuqing Wang; Huijun Le; Libo Liu; Yiding Chen; Bo Xiong; Ruilong Zhang; Bowei Liu; Wenbo Li; Wenjie Sun; Yu Li (Space Weather, 2025)
Abstract Using total electron content (TEC) data from multiple ground‐based Global Navigation Satellite System (GNSS) receiver networks from 2010 to 2023, we reconstructed ionospheric TEC maps for East Asia. The maps cover longitudes from 70°E to 150°E and latitudes from 20°S to 60°N. The time resolution of reconstructed TEC map was 15 min. The region with the best latitude coverage of GNSS TEC observations is found between 100°E and 110°E. Consequently, we used the TEC latitudinal profile data at 105° longitude for empirical orthogonal function decomposition, which allowed us to derive a set of orthogonal basis functions for the TEC latitudinal profile. Using these basis functions, we fitted the TEC latitude profile for each meridian plane. By combining the results from the TEC latitudinal profiles across all meridian planes from 70°E to 150°E, we created the regional TEC maps. Comparing the observed TEC data with the CODE TEC maps reveals that the CODE maps contain consistent errors in the East Asian sector, primarily due to limited data availability in this region, particularly in China. Furthermore, comparisons with Jason's TEC data over the oceans demonstrated that our reconstructed TEC map could still accurately reproduce the latitude profile, even with some missing data at some latitudes. This reconstructed regional TEC maps provide us a crucial data product that can assist us in statistically analyzing finer structural features of the ionosphere in this region.